Brown lines on nails as melanonychia striata: a case report and review - Irawan, Hendry (International Journal of Research in Medical Sciences, 2023)
Melanonychia striata is caused by the deposition of melanin as a result of melanocyte hyperplasia or increased melanocyte activity. Melanonychia striata has a similar appearance to a malignant lesion, so a proper diagnosis should be made to ensure appropriate management. A 28-year-old man had complained of black discoloration in the middle of the right toenail since a month ago. Previously, the patient frequently experience pain in the nail and redness at the nail tip. The patient had often worn small-size shoes. Physical examination revealed a line of blackish-brown lesions from the proximal to the distal nail plate, with clear boundaries, yellowish on the distal of the nail, and a sign of subsided inflammation on the edges of the nail. Nail extraction with roserplasty-technique and biopsy was conducted. The histopathological result supported the diagnosis of melanonychia striata. Then, the patient was treated with oral analgesic and antibiotic and discharged with no complications. This melanonychia striata case is accompanied by rapid progression and is most likely due to the proliferation of melanocyte cells. The surgical procedure with a partial or total nail extraction should be considered performed to treat the lesion and collect the sample for further examination. Histological examination is a gold standard to differentiate benign and malignant subungual lesions. Periodic follow-up is also necessary to assess the recurrence and general condition of the patient.